2018
DOI: 10.1007/s10797-018-9508-1
|View full text |Cite
|
Sign up to set email alerts
|

Inter vivos transfers of ownership in family firms

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Overwhelmingly, it is in the best interest of business owners to transfer their business to heirs before their death, as taxes can quickly accumulate and cut into the amount of assets being transferred (Giarmarco, 2012;Hines et al, 2018). Inter vivos gifting of the family business is just one way to enable ownership transfer as it can help to avoid taxes and penalties associated with inheritance (Hines et al, 2018), but such giving requires strict planning and confidence in the next generation. According to Vozikis et al (2012), the tax burden can be minimized for successors by using life insurance on incumbents of family businesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overwhelmingly, it is in the best interest of business owners to transfer their business to heirs before their death, as taxes can quickly accumulate and cut into the amount of assets being transferred (Giarmarco, 2012;Hines et al, 2018). Inter vivos gifting of the family business is just one way to enable ownership transfer as it can help to avoid taxes and penalties associated with inheritance (Hines et al, 2018), but such giving requires strict planning and confidence in the next generation. According to Vozikis et al (2012), the tax burden can be minimized for successors by using life insurance on incumbents of family businesses.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of roughly 1,700 German family firms found that transfer of ownership was easier for family firms who were more successful (Hines et al , 2018); most likely because more resources were available for planning and structuring the business for such a transfer. Hines et al (2018) found that ownership transfer occurred more frequently when market conditions were favorable. Under favorable market conditions, more assets were available to accommodate and fund the transfer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The regulation of family business, including the associated tax issues, is a broadly discussed issue (see, for instance, Hines et al, 2019;Chen et al, 2010;Shin, 2020;Steijvers and Niskanen, 2011;Vincencova et al, 2015). This fact stems from the social relevance of this type of business: family crafts and family business corporations are major employers and producers (Mandl, 2008).…”
Section: Discussion -Evaluation Of the Current De Lege Lata Legislati...mentioning
confidence: 99%
“…At the same time, a number of studies demonstrate that family businesses are more sensitive to the risk of agency costs, loss of reputation and thus less willing to apply a more aggressive approach to tax optimization (Chen, 2010). The thesis that family businesses in good economic conditions exhibit a higher rate of inter vivos transfer has been confirmed in some studies (for instance see Hines, 2019), with this phenomenon being significantly determined by related tax considerations.…”
Section: Selected Aspects Of the Operation And Transfer Of A Family B...mentioning
confidence: 95%
“…In other words, bequest motives drive short-term present economic decisions to be influenced by long-term future utility expectations. Bequest motives are also recognized by existing literature to exert influence on the current managerial behavior and future succession decisions of family businesses Ravikumar, 2001, 2004;Caselli and Gennaioli, 2013;Hines Jr, Potrafke, Riem, and Schinke, 2019). This stems from the most defining objective of family firms relative to non-family firms, i.e., the promotion of business wealth and influence of family members and future generations (Chua, Chrisman, and Sharma, 1999;Burkart, Panunzi, and Shleifer, 2003;Bennedsen, Perez-Gonzalez, and Wolfenzon, 2010).…”
Section: Introductionmentioning
confidence: 97%